COMPARISON OF GENDER PERFORMANCE ON AN INTELLIGENCE TEST AMONG MEDICAL STUDENTS - Ali, Muhammad Sohail; Suliman, Muhammad Imran; Kareem, Abida; Iqbal, Mariam (Journal of Ayub Medical College Abbottabad, 2009)
Background: Since the Government of Pakistan abolished the gender based system of admission to medical colleges, all colleges have seen a huge influx of female medical students, reaching up to 70- 80% of all students in some colleges. This trend is still persisting about 15 years after the decision. The objectives of the current study were to assess if there is any significant difference between male and female medical students in scores on a structured, standard, robust test of intellectual ability. Exact venue of the research is withheld for confidentiality. The study was carried out in 2003-2005. Methods: A cross-sectional, comparative study with sample size of 150 students, 75 male and 75 female students. Participants signed a consent form, were assessed on Raven’s Standard Progressive Matrices (SPM), and data was analysed using SPSS-12. Results: On the SPM test, the male students as a group, scored higher than the female students as a group, the difference was small but statistically significant (p=0.015). Conclusion: Performance on the SPM inclines in favour of the male gender group. More research needs to be carried out into the other possible factors that could explain the gender disparity in medical colleges in Pakistan. Keywords: Gender, intelligence, performance, IQ Scoring